Design and development of fuzzy logic controller for cascade control application. - Mohd Tarik, Mohammad Haizad (Universiti Teknologi PETRONAS, 2016)
Process control and automation are crucial as it enables manufacturers to produce an end product with desired quality and specification. Cascade control is one of the control strategy used in process control. However, most of the cascade control loop are controlled with PID controller which sometimes has a large settling and this will lead towards reduced efficiency of the process plant. This project aims to design and develop fuzzy logic controller to provide better control performance in cascade control. The proposed controller is simulated in MATLAB to evaluate its performances against the conventional controller. Simulation result shows the fuzzy controller can provide better control performance for both single-loop and cascade control compared to PID